2008
DOI: 10.1016/j.taap.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of the nerve gas sarin impairs ventilatory responses to hypercapnia and hypoxia in rats

Abstract: Sarin, a highly toxic nerve gas, is believed to cause bronchoconstriction and even death primarily through respiratory failure; however, the mechanism underlying the respiratory failure is not fully understood. The goals of this study were to ascertain whether sarin affects baseline ventilation (V E ) and V E chemoreflexes as well as airway resistance and, if so, whether these changes are reversible. Four groups of F344 rats were exposed to vehicle (VEH) or sarin at 2.5, 3.5, and 4.0 mg h m −3 (SL, SM, and SH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Peripheral muscarinic receptor overstimulation produces broncho-constriction, oedema and excess secretions, which have been demonstrated, in the case of sarin poisoning, to respond to treatment with the antimuscarinic atropine, although efficacy was limited at high challenge doses, 28,29 although studies in sarinexposed rats suggested that disruption of the central respiratory drive was responsible for respiratory failure and death. 30 A centrally mediated respiratory disorder has been shown to contribute in human OP poisoning cases, and some benefit from diazepam treatment was demonstrated. 31 In a practical poisoning scenario, personnel might not be aware that they have been exposed to nerve agent until early signs of poisoning manifest, by which time a significant degree of tissue AChE inhibition might be present.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral muscarinic receptor overstimulation produces broncho-constriction, oedema and excess secretions, which have been demonstrated, in the case of sarin poisoning, to respond to treatment with the antimuscarinic atropine, although efficacy was limited at high challenge doses, 28,29 although studies in sarinexposed rats suggested that disruption of the central respiratory drive was responsible for respiratory failure and death. 30 A centrally mediated respiratory disorder has been shown to contribute in human OP poisoning cases, and some benefit from diazepam treatment was demonstrated. 31 In a practical poisoning scenario, personnel might not be aware that they have been exposed to nerve agent until early signs of poisoning manifest, by which time a significant degree of tissue AChE inhibition might be present.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Chemosensory effects also proposed to contribute to CWNA-induced respiratory toxicity and may contribute to the acute effect following GD exposure. 43 With regard to the dose of GD, the most notable changes were observed in animals exposed to 841 mg/m 3 compared to 280 or 561 mg/m 3 GD exposures. Although not significant, mean MV, PIF, PEF, Ti, Te, EEP, pause, and Penh values showed dose-dependent changes with 280 or 561 mg/m 3 GD at 4 hours post-GD exposure that was reduced at 24 hours postexposure.…”
Section: Discussionmentioning
confidence: 94%
“…41,42 Chemosensory effects also proposed to contribute to CWNA-induced respiratory toxicity and may contribute to the acute effect following GD exposure. 43…”
Section: Discussionmentioning
confidence: 99%